Perpetua athlete of god - Gold, Barbara K. 1945- (New York Oxford University Press, 2018)
Perpetua's Passio: text, authorship, authenticity -- And I became male: gender and the athlete -- A matter of genre and influence: the Passio and Greco-Roman pagan and Christian narratives -- Carthage: pagan culture, religion, and society in the High Roman Empire -- Carthage: the early Christian community -- Perpetua's life: family (natal and Christian), education, and social status -- The conditions of martyrdom in the High Roman Empire -- The Nachleben of Perpetua: her unwitting legacy
Literaturverzeichnis: Seite 223-239
Keywords: Perpetua -- Saint -- -203; Perpetua; Saint; Christian women saints -- Biography; Christian women martyrs -- Biography; Christian women martyrs; Christian women saints; Biography; Biography; Biografie